The hormonal environment and estrogen receptor signaling alters Chlamydia muridarum infection in vivo - Gravitte, Amy; Kintner, Jennifer; Brown, Stacy; Cobble, Allison; Kennard, Benjamin; Hall, Jennifer V. (Frontiers in Cellular and Infection Microbiology, 2022)
Chlamydia is the most common bacterial sexually transmitted infection worldwide. Previous studies indicate that the progression of chlamydial infection is influenced by various factors, including the female sex hormones estrogen and progesterone. Sex hormone levels naturally fluctuate in women throughout their menstrual cycle. Varying concentrations of estrogen and progesterone may impact the progression of chlamydial infection and the host’s immune response to Chlamydia. Estrogen signals through estrogen receptors (ERs), ERα and ERβ. These receptors are similar in structure and function, but are differentially expressed in tissues throughout the body, including the genital tract and on cells of the immune system. In this study, we used ovariectomized (OVT) BALB/c mice to investigate the impact of long-term administration of physiologically relevant concentrations of estrogen (E2), progesterone (P4), or a combination of E2/P4 on the progression of and immune response to C. muridarum infection. Additionally, we used ERα and ERβ knockout C57/BL6 mice to determine the how ERs affect chlamydial infection and the resulting immune response. Estrogen exposure prevented C. muridarum infection in vaginally infected OVT mice exposed to E2 alone or in combination with P4, while OVT or Sham mice exposed to hormone free, P4 or depo-medroxyprogesterone acetate shed similar amounts of chlamydiae. The hormonal environment also altered T cell recruitment and IFNε production the genital tracts of infected OVT and Sham mice on day 10 post infection. The absence of ERα, but not ERβ, in ER knockout mouse strains significantly changed the timing of C. muridarum infection. ERαKO mice shed significantly more chlamydiae at day 3 post infection and resolved the infection faster than WT or ERβKO animals. At day 9 post infection, flow cytometry showed that ERαKO mice had more T cells present and targeted RNA sequencing revealed increased expression of CD4 and FOXP3, suggesting that ERαKO mice had increased numbers of regulatory T cells compared to ERβKO and WT mice. Mock and chlamydia-infected ERαKO mice also expressed more IFNε early during infection. Overall, the data from these studies indicate that sex hormones and their receptors, particularly ERα and ERβ, differentially affect C. muridarum infection in murine models of infection.